2004
DOI: 10.1111/j.1469-7610.2004.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Larger deficits in brain networks for response inhibition than for visual selective attention in attention deficit hyperactivity disorder (ADHD)

Abstract: The widespread hypoactivity for the ADHD children on the go/no-go task is consistent with the hypothesis that response inhibition is a specific deficit in attention deficit hyperactivity disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
199
3
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(235 citation statements)
references
References 132 publications
26
199
3
1
Order By: Relevance
“…39 In this study, we clearly find impaired activation in the right parietal cortex associated with mental rotation/spatial working memory in children with ADHD-CT. This is consistent with our previous study of adolescents with ADHD-CT 3 and with the recent study of Booth et al 20 showing impaired right parietal activation during a visual selective attention task in children with ADHD. This is also consistent with studies of event-related potentials (ERPs) which have shown reduced amplitudes to attentional orienting cues over posterior brain regions, consistent with dysfunction of the posterior parietal attentional system.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…39 In this study, we clearly find impaired activation in the right parietal cortex associated with mental rotation/spatial working memory in children with ADHD-CT. This is consistent with our previous study of adolescents with ADHD-CT 3 and with the recent study of Booth et al 20 showing impaired right parietal activation during a visual selective attention task in children with ADHD. This is also consistent with studies of event-related potentials (ERPs) which have shown reduced amplitudes to attentional orienting cues over posterior brain regions, consistent with dysfunction of the posterior parietal attentional system.…”
Section: Discussionsupporting
confidence: 93%
“…4 Importantly, there was no additional increased activation of diffuse and inefficient cortical attentional networks of the midline in the children with ADHD-CT, as has been shown in the adolescents with ADHD-CT. 3,40 This differs from previous reports of widespread diffuse and inefficient activation of brain areas in children with ADHD using 'go/no go' 8 and spatial orienting 4 fMRI tasks, but is consistent with recent reports using other fMRI tasks that are known to activate more specific brain areas. 20,41,42 The consistency of our findings across this and our previous study 3 may be due, in part, to ADHD samples that are homogeneous with respect to handedness, gender, age range and diagnosis (that is only ADHD-CT). Additionally, the specificity of our mental rotation fMRI task allows our interpretations to be constrained by known brain-behaviour relationships that exist from nonhuman primate work on spatial working memory.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…People with ADHD are less able to suppress prepotent motor responses in tasks such as the Go/No-Go and the Stop-Signal task (Oosterlaan, Logan, & Sergeant, 1998 ) , and, moreover, do not effectively engage right lateral prefrontal cortex in support of motor response inhibition in those same tasks (Booth et al, 2005 ;Tamm et al, 2004 ;Casey et al, 1997 ;Rubia et al, 2005 ) . If retrieval suppression engages response override mechanisms, people with attention defi cit disorder may show smaller negative control effects, and have diffi culty controlling unwanted memories.…”
Section: Attention Defi Cit Disordermentioning
confidence: 99%
“…Neuroimaging studies of attention defi cit disorder have shown that individuals with ADHD do not engage right lateral prefrontal cortex as effectively as controls during motor response suppression (Booth et al, 2005 ;Casey et al, 1997 ;Rubia et al, 1999 ;Rubia, Brammer, Tonne, & Taylor, 2005 ;Tamm, Menon, Ringel, & Reiss, 2004 ) . Based on the possibility that retrieval suppression may engage related response override mechanisms, used his face-scene think/no-think procedure to compare retrieval suppression in adults with and without attention defi cit disorder to determine whether the former suffers defi cits in retrieval suppression.…”
Section: Attention Defi Cit Disordermentioning
confidence: 99%